Daya Terima Dan Kandungan Gizi Keripik Umbi Rumput Teki (Cyperus Rotundus) Dalam Menambah Diversifikasi Pangan: The Acceptibility and Nutrient Content of Nut Grass Tuber (Cyperus rotundus) in Adding Food Diversification - Romalasari, Atika (Jurnal Agroindustri Terapan Indonesia, 2023)
Nut grass (Cyperus rotundus) is one of the grasses that very potential to be developed because abundant benefits. One potential of the nut grass that can be developed is the nut grass tuber chips. Chips Puzzles are savory snacks that are rich in nutrients just like any other snack. Nut grass tuber is tested organoleptic test which is hedonic test (preferably level) of flavor, color, crispness, aroma and overall appearance parameters. The hedonic test of the parameters of taste, color, crispness, aroma and overall appearance showed that the panelists liked the taste of the nut grass tuber with a hedonic score of 4.0 (like), color: 3.17, crispness: 2, 83 (quite like), aroma: 3.63 (like) and overall appearance: 3.47 (quite like). Nut grass tuber chips contain fat of 39.53%, protein of 4.61%, carbohydrate of 41.29%, water of 2.25%, ash of 4.89% and fiber of 6.05% per weight of material